Avaliação micológica bucal, achados ultrassonográficos de glândulas salivares e teste de qualidade de vida em pacientes com síndrome de Sjögren primária e secundária - Medeiros, Clarissa Castro Galvão (2016)
Sjögren's syndrome (SS) is a systemic autoimmune disease that affects mostly middle age women in a 9:1 ratio when compared to men. Although SS's inflammatory process can affect any organ, the most frequent symptoms are ocular and oral dryness due to lymphocytic infiltration of exocrine glands. The pathogenesis of this illness is not fully comprehended yet. SS can be classified as primary (pSS), when the patient does not present any concomitant autoimmune disease or secondary (sSS), when it is associated with other pathology of this nature. SS patients are more susceptible to oral complications due to hyposalivation. This study evaluated patients with pSS, sSS and healthy individuals considering the following aspects: non-stimulated salivary flow, colonization pattern of yeast in the oral cavity, salivary glands ultrasonographic findings and impact of oral health on quality of life. The information obtained was compared between the experimental groups. SS patients presented a decreased salivary flow rate when compared to the controls. Inverse relationships between age and salivary flow rate in all groups and between time since SS diagnosis and salivary flow rate among pSS and pSS groups were observed. A chromogenic medium was used for yeast culturing and presumptively identification of the species. Molecular identification performed by polymerase chain reaction (PCR), DNA sequencing and phylogenetic analysis recognized 11 species from six different genera. C. albicans was the most prevalent species in all groups followed by C. tropicalis, C. glabrata, C. parapsilosis and C. krusei. Total CFU/mL and C. albicans counts were higher in the pSS and sSS patients when comparing them to the control group. An inverse relationship between age and salivary flow rate and between salivary flow rate and the occurrence of C. albicans, C. tropicalis and C. glabrata occured in all groups. Although healthy individuals presented a greater variety of species in the oral cavity, SS patients had a higher CFU's count, as well as a higher incidence of clinical manifestations of candidiasis. No statistically significant difference was detected among the three groups when the scores of the questionnaire OHIP-14 were compared. The most frequent alteration detected during ultrasonography examination was inhomogeneous echogenicity of at least one of the parotid and/or submandibular glands followed by decreased gland size and the presence of multiple small oval hypoechoic areas.